Fetomaternal outcome in sickle cell disease in a tertiary care centre - Modi, Rahi S.; Patel, Srushti S.; Modi, Dipti A.; Talesara, Heena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Sickle cell disease is a hereditary haematological disorder prevalent in tribal regions of India. Sickle cell disease can increase complications during pregnancy and in turn negatively influence pregnancy outcomes. This study reports the analysis of tribal maternal admissions in the tertiary centre S.S.G. Hospital, Baroda, Gujarat. Hence this study was conducted to assess complications in pregnancy and maternal and perinatal outcome among women with Sickle cell disease. Methods: It was a retrospective observational study including all pregnant women with sickle cell disease after 20 weeks of gestation who delivered at S.S.G. Hospital, Baroda from August 2019 to August 2020. Results: There were 43 antenatal women with Sickle cell disease during the study period. There was increased risk of obstetric complications like gestational hypertension (11.62%), preeclampsia (9.3%), eclampsia (6.97%), HELLP syndrome (4.65%), intrauterine growth retardation (23.25%), and oligohydramnios (11.62%). Medical complications observed were mainly anaemia (53.48%), vaso-occlusive crisis (18.16%), acute chest syndrome (4.65%) and infections like urinary tract infection (6.97%) and pneumonia (4.65%). The incidence of low birth weight babies (56.94%), low APGAR score (11.62%) and neonatal ICU admissions (23.25%) was high. 6.5% cases of maternal mortality and 4.65% cases of perinatal mortality was observed. Conclusions: Pregnancy in Sickle cell disease is associated with an increased maternal morbidity and high perinatal mortality due to obstetric and medical complications.